Penerapan Keadilan dalam Penafsiran Unsur Pembuktian Tidak Sederhana Pada Pengembang (Developer) Selaku Debitor Pailit dalam Rangka Melindungi Kepentingan Hukum Kreditor - Hermawan, Vincent; Adam, Richard C. (AL-SULTHANIYAH, 2025)
This study analyzes the application of justice in the interpretation of the not-simple proof element in developer bankruptcy cases to protect both debtor and creditor legal interests. Using normative legal research with conceptual and statutory approaches, the study finds a shift in court decisions from legal formalism to substantive justice, particularly since the issuance of Supreme Court Circular Letter No. 3 of 2023. This change effectively protects developers from premature bankruptcy, in line with legal theories of Radbruch and Aristotle and global trends of prioritizing business continuity. However, this shift paradoxically creates a legal dilemma for creditors, who lose access to a quick and efficient mechanism for debt settlement, thus compromising their legal certainty and benefits. This research concludes that a balance between protecting both parties is a crucial issue, and future studies should explore alternative dispute resolution mechanisms to ensure a more equitable and efficient legal system for all stakeholders.